Housing differentiation and housing poverty in Chinese low-income urban neighborhoods under the confluence of State-market forces. Issue 5 (28th May 2017) - He, Shenjing; Liu, Lin; Yang, Gangbin; Wang, Fenglong
ABSTRACT: Based on a large-scale household survey conducted in six large Chinese cities, this study is among the first attempts to juxtapose factors related to institution, market, and demography to examine the complex patterns and mechanisms of housing differentiation and housing poverty in low-income neighborhoods, which are conventionally conceived as homogenous substandard settlements. Results of Theil indices and multivariate regression models convey several interesting findings. First, the forces of the market and the State have projected different impacts on various aspects of housing status. Institutional factors had significant impacts on some costly and durable housing indicators such as housing tenure and housing area, while market forces have swiftly transformed the most malleable aspects of housing conditions, such as housing facilities, and will eventually replace some institutional legacies. Second, within-group housing differentiation is more palpable than between-group housing differentiation, suggesting that low-income neighborhoods in large Chinese cities are fluid and heterogeneous. Third, different institutional elements have different impacts on housing poverty. The well-functioning market remuneration system helps reduce the risk of housing poverty, yet working poor remains a severe problem. These findings can inform policies promoting social mix and housing affordability.